2012
DOI: 10.1002/cbic.201200471
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis and Enzymatic Testing of CMP‐Sialic Acid Derivatives

Abstract: The cycloSal approach has been used in the past for the synthesis of a range of phosphorylated bioconjugates. In those reports, cycloSal nucleotides were allowed to react with different phosphate nucleophiles. With glycopyranosyl phosphates as nucleophiles, diphosphate-linked sugar nucleotides were formed. Here, cycloSal-nucleotides were used to prepare monophosphate-linked sugar nucleotides successfully in high anomeric purity and high chemical yield. The method was successfully used for the synthesis of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
3
19
0
2
Order By: Relevance
“…The biochemical and/or physiological basis for such significant differences in activity is/are not yet clear, but they clearly validate the effort devoted to diastereoselective syntheses and justify additional research into the cycloSal prodrugs. Applications of the cycloSal group as a leaving group in synthesis of 1,6-diglycopyranosyl-phosphates only further enhances the value of this group [75,76]. …”
Section: Ester Prodrugsmentioning
confidence: 99%
“…The biochemical and/or physiological basis for such significant differences in activity is/are not yet clear, but they clearly validate the effort devoted to diastereoselective syntheses and justify additional research into the cycloSal prodrugs. Applications of the cycloSal group as a leaving group in synthesis of 1,6-diglycopyranosyl-phosphates only further enhances the value of this group [75,76]. …”
Section: Ester Prodrugsmentioning
confidence: 99%
“…Furthermore, NDP‐sugars have been post‐synthetically modified 13. Recently we showed that the method can also be used for the synthesis of NMP‐sugars, for example, N ‐acetylneuraminic acid (derivatives) 14…”
Section: Resultsmentioning
confidence: 99%
“…The NMR data is consistent with literature. [28] Methyl (Prop-2-ynyl 5-acetamido-3,5-dideoxy-d-glycero-a-dgalacto-2-nonulopyranosid)onate (3) Am ixture of 2 (2.81 g, 5.5 mmol), AgOTf (2.1 g, 8.2 mmol) and powdered 4 molecular sieves (4 g) in freshly distilled propargyl alcohol (60 mL) was stirred at room temperature under an Ar atmosphere. The reaction mixture was protected from light and stirred for 2h in the dark.…”
Section: Synthesis Of Propargyls Ialoside (4)mentioning
confidence: 99%